Raw ship-based Multibeam Sonar Data from the Amundsen Sea acquired during R/V Nathaniel B. Palmer expedition NBP0702 (2007) (IEDA: Marine-Geo Digital Library, 2007)
This data set was acquired with a ship-based Kongsberg EM120 Multibeam Sonar system during Nathaniel B. Palmer expedition NBP0702 conducted in 2007 (Chief Scientist: Dr. Stan Jacobs; Investigator(s): Dr. Frank Nitsche). These data files are of MBSystem Compatible format and include Acoustic Backscatter, Swath Bathymetry, and Sidescan data that have not been processed. Data were acquired as part of the project(s): The Amundsen Continental Shelf and the Antarctic Ice Sheet, and funding was provided by NSF grant(s): ANT04-40775.